komunikasi Persepsi Wanita yang Dipoligami: Studi Komunikasi Interpersonal pada Masyarakat Kecamatan Sagulung Kota Batam - Hasan, Al Mukarromah (Program Studi Komunikasi dan Penyiaran Islam, 2024)
Polygamy has always been a topic that triggers various opinions in marriage systems around the world. The religion of Islam and the Indonesian state itself stipulate the terms and conditions for practicing polygamy. Many women have to face polygamy under various conditions: some accept it unwillingly, some accept it sincerely, and some strongly oppose this situation. This study aims to uncover the lived experiences of women who experience polygamy through their perceptions of life while undergoing polygamy. This research method uses a qualitative approach with a phenomenological approach. Data collection techniques include observation, interview, and documentation, with informants who are women who experience polygamy, especially in Sagulung Sub-district, Batam City. The results showed that women's perceptions of polygamy, based on Abraham Maslow's five theories, indicate that women often experience dissatisfaction in fulfilling physical needs, affection, love, protection, as well as feelings of not being considered as a life partner and self-actualization.